The Effectiveness of Information Service Using Contextual Teaching and Learning In Preventing Sexual Abuse - Annajmi Alfath; Firman Firman; Syahniar Syahniar (International Journal of Research in Counseling and Education, 2018)
Adolescent sexual behavior that does not comply with the values and norms will lead to sexual abuse. Causes of sexual abuse is the lack of knowledge and adolescent sex education obtained. Knowledge and adolescent sex education can be obtained through counselor. Counselor an important role to provide education and knowledge of sex, because half the time teenagers at school. In providing new knowledge counselor can use contextual teaching and learning, it is intended that the material provided can be understood by students. The study discussed of the efektiveness of information service contextual teaching and learning to prevent sexual abuse of a senior high school students by using the sexual abuse scale. Data analysis technique used were Kolmogorov Smirnov 2 Independent Sample and Wilcoxon Signed Rank Test.The result indicated that overall the sexual abuse students can be prevented by the information service used contextual teaching and learning. The implication of the study might be useful as an innovation for counselor serivice on senior high school.